STRUCTURAL INVOLUTION AND REMODELING OF LYMPH NODES IN RHEUMATOID ARTHRITIS (Global Conference on Medical and Health Sciences, 2026)
The aim of the study was to morphometrically assess age-related morphofunctional changes in lymph nodes, including structural remodeling associated with increased stromal components and medullary zone reduction, in 18-month-old albino rats under chronic rheumatoid arthritis conditions, and to compare the findings with a control group.